2015
DOI: 10.1371/journal.pone.0139014
|View full text |Cite
|
Sign up to set email alerts
|

Weight Growth Velocity and Neurodevelopmental Outcomes in Extremely Low Birth Weight Infants

Abstract: IntroductionThis study aimed to assess whether weight growth velocity (WGV) predicts neurodevelopmental outcomes in extremely low birth weight infants (ELBWIs).MethodsSubjects were infants who weighed 501–1000 g at birth and were included in the cohort of the Neonatal Research Network of Japan (2003–2007). Patel’s exponential model (EM) method was used to calculate WGV between birth and discharge. Assessment of predictions of death or neurodevelopmental impairment (NDI) was performed at 3 years of age based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…[ 31 , 50 56 ] Poor growth velocity during hospitalization (EUGR) was also related to poor psychomotor outcome in early childhood. [ 25 , 34 , 43 , 57 , 58 ] Thus, early and aggressive nutritional support for adequate body weight gain during hospitalization in VLBW infants, which may mitigate the risks of neurodevelopmental disorders, appears to be the current consensus of opinion in the literature. [ 25 , 43 , 57 59 ] In our study, after adjusting for SGA and EUGR, failure to thrive after discharge was still an independent factor for poor neurodevelopmental outcomes in the VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 , 50 56 ] Poor growth velocity during hospitalization (EUGR) was also related to poor psychomotor outcome in early childhood. [ 25 , 34 , 43 , 57 , 58 ] Thus, early and aggressive nutritional support for adequate body weight gain during hospitalization in VLBW infants, which may mitigate the risks of neurodevelopmental disorders, appears to be the current consensus of opinion in the literature. [ 25 , 43 , 57 59 ] In our study, after adjusting for SGA and EUGR, failure to thrive after discharge was still an independent factor for poor neurodevelopmental outcomes in the VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of certified psychologists who evaluated the KSPD was limited, even at levels 2-3 NICUs in Japan. All of these issues are related to a high rate of missing follow-up data, which was commonly observed in previous research using NRNJ registry data [2,24] . We assumed that the reasons for missing data were not related to events or outcomes (i.e., mode of delivery or neurodevelopment), and we analyzed data of patients with a complete set of data (i.e., complete case analysis).…”
Section: Discussionmentioning
confidence: 92%
“…This could be related to difficulty in optimizing energy in PN due to glucose and lipid intolerance, poor caloric and protein delivery that occurs while feeds are being advanced and PN is weaned, as well as increased metabolic demands . Infants with EUGR are at risk for poorer neurodevelopmental outcomes, worsened neonatal intensive care unit (NICU) outcomes, and adult‐onset disease …”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 Infants with EUGR are at risk for poorer neurodevelopmental outcomes, worsened neonatal intensive care unit (NICU) outcomes, and adult-onset disease. [12][13][14][15][16] Studies have shown that the use of preterm feeding protocols in the NICU can improve feeding tolerance and decrease the risk for NEC. [17][18][19] They have also shown reduced PN use and days to full feeds, reduced late-onset sepsis, fewer line days, and improved growth.…”
Section: Introductionmentioning
confidence: 99%